2005
DOI: 10.1016/j.joca.2004.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Subchondral and trabecular bone metabolism regulation in canine experimental knee osteoarthritis

Abstract: Intense bone remodeling takes place in both subchondral and trabecular bone in the knee following ACL transection. This process seems to occur around week 12, although Oc and NO appeared to be involved earlier at 8 weeks. These results suggest that not only subchondral but also trabecular bone metabolism is altered in this OA model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 58 publications
4
34
0
Order By: Relevance
“…We thenceforth maintained cells for 36 days in basal media and OM+ media and observed that trabecular osteoblasts exhibited greater ALP activities under basal and osteogenically stimulated conditions, further emphasising the inherent diversity in osteoblasts from these distinct bone types. Indeed, they are likely consistent with studies revealing different differentiation capacity in bone from neighbouring locations within single OA patient groups (Hilal et al, 2001;Lavigne et al, 2005;Westacott et al, 1997) and with recent studies describing distinct function and molecular properties in human haematopoietic stem cells in trabecular bone compartments from those located deeper in the marrow (Guezguez et al, 2013). Our studies highlight that osteoblasts from the different bone types showed matching disparity in both OA and OP patients.…”
Section: Shah Et Al Bone Type-related Differences In Human Osteoblsupporting
confidence: 92%
See 1 more Smart Citation
“…We thenceforth maintained cells for 36 days in basal media and OM+ media and observed that trabecular osteoblasts exhibited greater ALP activities under basal and osteogenically stimulated conditions, further emphasising the inherent diversity in osteoblasts from these distinct bone types. Indeed, they are likely consistent with studies revealing different differentiation capacity in bone from neighbouring locations within single OA patient groups (Hilal et al, 2001;Lavigne et al, 2005;Westacott et al, 1997) and with recent studies describing distinct function and molecular properties in human haematopoietic stem cells in trabecular bone compartments from those located deeper in the marrow (Guezguez et al, 2013). Our studies highlight that osteoblasts from the different bone types showed matching disparity in both OA and OP patients.…”
Section: Shah Et Al Bone Type-related Differences In Human Osteoblsupporting
confidence: 92%
“…Cells with disparate origins, such as trabecular and cortical bone, are also used somewhat interchangeably, to inform understanding of skeletal biology. Although all bone exhibits some highly conserved factors in its development, remodelling and repair, it is also apparent that the response to many in vivo challenges is not always identical in trabecular, cortical and subchondral bones types (Lavigne et al, 2005;Simon et al, 2008;Wade-Gueye et al, 2010). Differences in osteoblasts derived from long bone and calvarial sites, including distinct transcriptional signatures, have been described in vitro (Akintoye et al, 2006;Rawlinson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was observed that in tissue extracted from subjects with OA the probability of indenting a SO was higher than a PL. It has been suggested that an increment of bone remodelling is seen in osteoarthritic subjects (Bailey et al, 2004;Bettica et al, 2002;Lavigne et al, 2005). Consequently, hypothetically osteoarthritic bone tissue might be composed of a larger number of younger, less mineralised and less hard structures.…”
Section: Discussionmentioning
confidence: 99%
“…The indirect role of osteoclasts in cartilage remodelling in response to mechanical stress has been observed using different osteoclast-blocking agents 18 28 31. Blocking bone resorption prevented OA progression in rats treated with a high dose of alendronate16 and in dogs receiving licofelone 2.…”
Section: Discussionmentioning
confidence: 99%